Ģimeņu ekonomiskās situācijas radīto atšķirību mazināšana sociālā pedagoga darbībā Ādažu vidusskolā 4. klasēs - Jaunupe, Līga (Latvijas Universitāte, 2008)
Diplomdarba temats: „Ģimeņu ekonomiskās situācijas radīto atšķirību mazināšana sociālā pedagoga darbībā Ādažu vidusskolā 4. klasēs”. Pētāmās problēmas būtība- sociālās nevienlīdzības radītās problēmas un to negatīvā ietekme uz skolēnu savstarpējām attiecībām. Pētījuma mērķis: mazināt ģimeņu ekonomiskās situācijas radītās atšķirības Ādažu vidusskolā 4. klasēs. Pētījuma praktiskajā daļā tiek aprakstīta sociālpedagoģiskā darbība ģimeņu ekonomiskās situācijas radīto atšķirību mazināšanā, iegūtie rezultāti un to analīze, kas ļauj secināt, ka pētījuma mērķis ir sasniegts un hipotēze apstiprinājusies, jo praktisko nodarbību rezultātā ir uzlabojusies skolēnu vērtību sistēma. Pētījumā izmantotās metodes: literatūras analīze novērošana intervēšana modelēšana sociālpedagoģiskā izmēģinājuma darbība Atslēgvārdi: ģimene, skolēnu savstarpējās attiecības, sociālā nevienlīdzība, sociālpedagoģiskā darbība, vērtības

Title of the diploma paper: “Reducing the differences created by the economic circumstances of the families through the interventions of the social teacher amongst the pupils of the 4th forms of Adazi Secondary School”. This study explores problems created by the social inequalities and the negative effect of these problems on the interpersonal relationships of the pupils. The research aim: To reduce the effects of the differences created by the economic circumstances of the families on the pupils of the 4th forms at Adazi Secondary School. The practical section of this paper describes socio-pedagogic interventions carried out to reduce the differences amongst pupils, created by the economic circumstances of their families. Presented results and analysis lead to the conclusion that the study aim has been achieved and hypothesis confirmed- pupils’ value systems have improved as a result of the practical interventions of the social teacher. Methods: •Literature review •Observations •Interview •Modelling •Socio-pedagogic pilot action Keywords: family, pupils’ interpersonal relationships, social inequalities, , socio-pedagogic work, values.
Decreasing the differences created by economic situations of the families in the work of the social pedagoguein Grade 4 at Ādaži Secondary school
Keywords: Pedagoģija